Triglyceride-glucose index and mortality risks in Helicobacter pylori-infected patients: a national cohort study - Yue Cao; Lingxiao Li; Feipeng Qiu; Weixing Wen; Hao Zhang; Yangxin Chen; Xiaoyan Cai; Yuli Huang (BMC Infectious Diseases)
Abstract Background While Helicobacter pylori (H. pylori) infection is associated with insulin resistance and higher mortality, research on insulin resistance indices and outcomes in H. pylori-infected patients is scarce. This study examines the association between the triglyceride-glucose (TyG) index, an insulin resistance marker, and all-cause and cardiovascular mortality in these patients. Methods This study analyzed NHANES 1999–2000 data to assess the association between the TyG index and all-cause and cardiovascular mortality in H. pylori-infected patients using weighted Cox models and restricted cubic spline analysis. Results Among 627 participants with a median follow-up of 20.8 years, 108 all-cause and 28 cardiovascular deaths occurred. Cox models showed that TyG was linked to a hazard ratio (HR) of 1.70 for all-cause mortality (95% CI: 1.23–2.34, P < 0.01) and an HR of 2.90 for cardiovascular mortality (95% CI: 1.91–4.42, P < 0.001). Restricted cubic spline analysis confirmed a linear relationship between the TyG index and both mortality risks. Stratified analyses showed that this relationship was significantly associated in most subgroups, but there was no significant interaction. Conclusion Higher TyG index is strongly linked to increased risks of both all-cause and cardiovascular mortality in H. pylori-infected patients.